2015
DOI: 10.1016/j.apsoil.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Short-term mesofauna responses to soil additions of corn stover biochar and the role of microbial biomass

Abstract: A B S T R A C TBiochar additions have been suggested to influence soil microbial communities that, through a cascade effect, may also impact soil fauna. In turn, any direct biochar effects on fauna can influence microbial communities through grazing, physical fragmentation of organic debris (and biochar) and modifying soil structure. If biochar creates a favorable environment for soil microorganisms, it is also plausible for fauna to be attracted to such microbially enriched habitats. However, how soil fauna r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…Domene et al (2014) indicated that microbial abundance could increase from 366.1 (control) to 730.5 μg C g −1 after an addition of 30 t ha −1 biochar. Similarly, microbial abundance increased by 5-56 % with the increase of corn stover biochar rates (from 0 to 14 %) for the different preincubation times (2-61 days) (Domene et al 2015). Some possible reasons may be responsible for the increase of microbial abundance, such as higher availability of nutrients or labile organic matter on biochar surface (Pietikäinen et al 2000;Bruun et al 2012), less competition (Lehmann et al 2011), the enhanced habitat suitability and refuge (Pietikäinen et al 2000;Warnock et al 2007), the increased water retention and aeration (Wardle et al 1999;Schimel et al 2007), or positive priming (Zimmerman et al 2011).…”
Section: Influence Of Biochar On Microorganisms Communitymentioning
confidence: 93%
“…Domene et al (2014) indicated that microbial abundance could increase from 366.1 (control) to 730.5 μg C g −1 after an addition of 30 t ha −1 biochar. Similarly, microbial abundance increased by 5-56 % with the increase of corn stover biochar rates (from 0 to 14 %) for the different preincubation times (2-61 days) (Domene et al 2015). Some possible reasons may be responsible for the increase of microbial abundance, such as higher availability of nutrients or labile organic matter on biochar surface (Pietikäinen et al 2000;Bruun et al 2012), less competition (Lehmann et al 2011), the enhanced habitat suitability and refuge (Pietikäinen et al 2000;Warnock et al 2007), the increased water retention and aeration (Wardle et al 1999;Schimel et al 2007), or positive priming (Zimmerman et al 2011).…”
Section: Influence Of Biochar On Microorganisms Communitymentioning
confidence: 93%
“…Another study conducted on collembolans (Protaphorura fimata) evaluated the effects of maize and wood biochars in a greenhouse experiment and revealed that P. fimata were not affected by the different biochars (Reibe et al, 2015). In Domene et al (2015), the behavior of two mesofauna species (enchytraeids and collembolan) was assessed as a result of corn stover biochar additions to a loamy soil. Enchytraeids did not show any avoidance or preference behavior compared to the unamended soil, while collembolans showed avoidance responses.…”
Section: Soil Biological Propertiesmentioning
confidence: 99%
“…Few studies have investigated the meso-fauna (Domene et al, 2015;Lehmann et al, 2011), both in terms of abundance/community and evaluation of biochar toxicity. Zhang et al (2013a) observed no variation in total nematode abundance following a wheat straw biochar addition (2.4 t ha À1 ), although higher diversity with the biochar addition was observed as well as an increased abundance of fungivores.…”
Section: Soil Biological Propertiesmentioning
confidence: 99%
“…If growth responses to BC and SMS treatments are mainly due to nutrient provision, then a saturation of plant nutrient demands will often result in a non-additive positive effect on plant growth (e.g., [63]), and may lead to a decline in plant growth at high levels [28] (p. 46). Alternatively, the combination of BC and SMS may have resulted in an oversupply of toxic elements (e.g., Al, Pb, Mn, As), or nutrients required at only very low levels (e.g., Mn, B) [3,23,25,64,65]. For example, high amounts of Mn are present in the BC used in our experiment (Table 1); while Mn is important for plant growth as a micronutrient [66], it can be toxic to plants at amounts that are highly variable between plant species [67] and environmental conditions [68][69][70].…”
Section: Discussionmentioning
confidence: 99%